1996
DOI: 10.1126/science.273.5274.464
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mimicry of a Protein Hormone by a Peptide Agonist: The EPO Receptor Complex at 2.8 Å

Abstract: The functional mimicry of a protein by an unrelated small molecule has been a formidable challenge. Now, however, the biological activity of a 166-residue hematopoietic growth hormone, erythropoietin (EPO), with its class 1 cytokine receptor has been mimicked by a 20-residue cyclic peptide unrelated in sequence to the natural ligand. The crystal structure at 2.8 A resolution of a complex of this agonist peptide with the extracellular domain of EPO receptor reveals that a peptide dimer induces an almost perfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
438
0
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(463 citation statements)
references
References 61 publications
18
438
0
7
Order By: Relevance
“…This assumes that the receptors follow the structural pattern that has been observed in the GHR, PRLR, and EpoR, the class 1 cytokine receptors for which structures are known (de Vos et al, 1992;Livnah et al, 1996). For IL-6 and CNTF, such a three-site cytokine/receptor binding model is consistent with mutagenesis data and the finding that the ternary receptor-complexes of IL-6 (Ward et al, 1994b;Paonessa et al, 1995) and CNTF are hexameric (cf.…”
Section: The Complex Of Growth Hormone and Its Receptorsupporting
confidence: 54%
See 2 more Smart Citations
“…This assumes that the receptors follow the structural pattern that has been observed in the GHR, PRLR, and EpoR, the class 1 cytokine receptors for which structures are known (de Vos et al, 1992;Livnah et al, 1996). For IL-6 and CNTF, such a three-site cytokine/receptor binding model is consistent with mutagenesis data and the finding that the ternary receptor-complexes of IL-6 (Ward et al, 1994b;Paonessa et al, 1995) and CNTF are hexameric (cf.…”
Section: The Complex Of Growth Hormone and Its Receptorsupporting
confidence: 54%
“…The structures of the class I cytokine receptors solved to date, GHR (de Vos et al, 1992), PRLR , and EpoR (Livnah et al, 1996) all show an angle of -90' between the two FN 111 domains of the CBD. Although there is a slight variation in the orientation of the two FN 111 domains in the CBDs relative to one another (a translation of 2-5 8, and a rotation of 8-12') (Livnah et al, 1996;Wells and de Vos, 1996), the receptors bind their ligands through the same loop regions (Livnah et al ., 1996). There is a similar conservation of the angle between the two FN 111 domains of the binding domain in the (Hibi et al, 1990).…”
Section: The High Affinity Ternary Il-6 Receptor-complex Is a Hexamermentioning
confidence: 96%
See 1 more Smart Citation
“…Structural and biochemical analyses have demonstrated that epo induces receptor dimerization (Barber et al, 1994;Livnah et al, 1996;Matthews et al, 1996;Watowich et al, 1992Watowich et al, , 1994. The dominant action of mutant receptors in J2E cells suggests that they heterodimerize with wild type receptors upon ligand binding, thereby altering normal receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…4c). The WSXWS motif is found in class 1 cytokine receptors [156]. In IL-10R1, the HSQWT sequence divides the G strand of D1 domain in two equivalent sub-parts, named G1 and G2 [117].…”
Section: The Il-22/il-22bp Structure and Interfacesmentioning
confidence: 99%